CTRA: A complex terrain region-avoidance charging algorithm in Smart World. (1st February 2020) - Han, Guangjie; Guan, Haofei; Zhou, Zeren; Li, Zhifan; Chan, Sammy; Zhang, Wenbo
Abstract: The emergence of "Smart World" is set to enhance daily necessities with abilities of sensing, communication, computation and intelligence so that many tasks and processes could be simplified, and made more efficient and enjoyable. The realization of Smart World requires information sensing as the foundation of future applications, thus wireless sensor networks (WSNs) are highly called for deployment. However, the limited energy of nodes has always restricted the application of WSNs. Wireless rechargeable sensor networks (WRSNs) introduce mobile chargers in WSNs to provide energy to low-powered sensor nodes through wireless charging technologies, thus solving energy problems effectively. Many studies have designed charging algorithms in normal environment without considering terrain complexity. The complex terrain causes difficulties in the movement and the path planning of the charger. In this paper, we propose a complex terrain region-avoidance charging algorithm (CTRA) in WRSNs. The algorithm aims to optimize the node energy replenishment, minimize the energy consumption of nodes in complex terrain and reduce the frequency the charger visits the complex terrain. The CTRA comprises three parts: the network is divided into small charging regions based on terrain complexity; nodes are classified into three classes based on the terrain where they are located, and different data routing protocols are designed for different classes of nodes in order to reduce the energy consumption on nodes in complex terrain areas; three charging schemes are designed in different terrain areas for the mobile charger. Simulation experiments indicate that the charging efficiency of the CTRA is greatly improved, and the number of dead nodes are also reduced effectively. Highlights: Wireless rechargeable sensor networks provide energy for sensor nodes and contribute to the development of the Smart World . Many studies have designed charging algorithms in the common network area without considering terrain complexity. In this paper, we propose a complex terrain region-avoidance charging algorithm (CTRA) in WRSNs. The algorithm aims to optimize the complex terrain problem in WRSNs, which may have great effects on mobile chargers. Simulation experiments indicate that the efficiency of the CTRA is greatly improved, and the death rate of nodes is reduced.